Effect of Interactions Between Endothelial Lipase Gene Polymorphisms and Traditional Cardiovascular Risk Factors on Coronary Heart Disease Susceptibility - Chunhui He; Xingming Song; Ting He; Qing Tian; Yuhui Zhang; Halisha Airikenjiang; Dilihumaer Abulaiti; Haitang Qiu; Mengbo Zhu; Juan Yang; Jian Zhang; Ying Gao (Reviews in Cardiovascular Medicine)
Background: Coronary heart disease (CHD) arises from a complex interplay of genetic and environmental factors. This study examines the influence of endothelial lipase gene polymorphisms (rs2000813 and rs3813082) and their interactions with traditional cardiovascular risk factors on CHD susceptibility. Methods: This retrospective case–control study enrolled 900 CHD patients and 900 control subjects. We evaluated associations between conventional cardiovascular risk factors and polymorphisms at the rs2000813 and rs3813082 loci in the endothelial lipase gene. Multifactorial analysis was used to assess interactions between traditional risk factors and these polymorphisms. Additionally, we developed a predictive model integrating genetic variants and clinical variables to estimate CHD risk. Results: No significant differences were observed in the distribution of rs2000813 genotypes (CC, CT, TT) and alleles (C, T), or rs3813082 genotypes (AA, AC, CC) and alleles (A, C) between CHD and control groups, including among males. However, in females with CHD, the rs2000813CT genotype was significantly more frequent (49.30%) than in controls (37.80%), whereas the CC genotype was less frequent in the CHD group (45.00%) than in controls (55.20%). Multivariate logistic regression identified the rs2000813CT genotype, hypertension, ages ≥60 years, body mass index (BMI) values ≥28 kg/m2, total cholesterol (TC) ≥6.2 mmol/L, and apolipoprotein B (ApoB) ≥1.1 g/L as potential risk factors for CHD in women (p < 0.05). Gene–environment interaction analysis revealed that BMI exerted the greatest influence (12.62%). A predictive model incorporating rs2000813 genotypes estimated CHD risk in women with an area under the curve (AUC) of 0.804. Conclusions: The rs2000813CT endothelial lipase genotype is potentially associated with an increased CHD risk in females, whereas the CC genotype may confer a protective effect. Integrating endothelial lipase gene variants with traditional cardiovascular risk factors enhances CHD risk prediction in women. Synergistic interaction between endothelial lipase polymorphisms and environmental factors appears to influence CHD occurrence in this population.